2022
DOI: 10.3390/sym14020328
|View full text |Cite
|
Sign up to set email alerts
|

A Collective Anomaly Detection Technique to Detect Crypto Wallet Frauds on Bitcoin Network

Abstract: The popularity and remarkable attractiveness of cryptocurrencies, especially Bitcoin, absorb countless enthusiasts every day. Although Blockchain technology prevents fraudulent behavior, it cannot detect fraud on its own. There are always unimaginable ways to commit fraud, and the need to use anomaly detection methods to identify abnormal and fraudulent behaviors has become a necessity. The main purpose of this study is to use the Blockchain technology of symmetry and asymmetry in computer and engineering scie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 27 publications
0
1
0
Order By: Relevance
“…Cluster analysis has also been used in supporting consensus protocols [152][153][154][155][156][157][158][159][160] For example, Khenfouci et al [125], to avoid data tampering and fraudulent activities, developed a customized clustering-based consensus protocol to carry out a decentralized consensus mechanism, according to which the k-Means was applied locally by multiple competitive miners. The methodology comprised four layers (i.e., data layer, network layer, blockchain layer, and machine learning layer) and had two main actors: management and miner.…”
Section: Category 1: Solitary Implementation Of Unsupervised Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…Cluster analysis has also been used in supporting consensus protocols [152][153][154][155][156][157][158][159][160] For example, Khenfouci et al [125], to avoid data tampering and fraudulent activities, developed a customized clustering-based consensus protocol to carry out a decentralized consensus mechanism, according to which the k-Means was applied locally by multiple competitive miners. The methodology comprised four layers (i.e., data layer, network layer, blockchain layer, and machine learning layer) and had two main actors: management and miner.…”
Section: Category 1: Solitary Implementation Of Unsupervised Learningmentioning
confidence: 99%
“…The final number of clusters was determined through optimal clustering, where the sum of square distances within clusters played the role of the performance index. The trimmed k-Means was also used in [160] to develop a collective anomaly detection approach, diverging from the conventional methods in that instead of implementing anomaly detection considering individual addresses and wallets, the study focused on scrutinizing anomalies at the user level, where the available dataset was taken from Kondor et al [161]. An interesting result of the study indicated that anomalies were more conspicuous among users with multiple wallets.…”
Section: Category 1: Solitary Implementation Of Unsupervised Learningmentioning
confidence: 99%
“…Many techniques have been developed for bitcoin fraud detection apart from the usage of timestamp data such as clustering [8], various techniques such as trimmed k-means, DBSCAN etc. are tested to this end.…”
Section: Related Workmentioning
confidence: 99%
“…Even if the ledger transparency featured by public blockchains mitigates the risk of fraudulent behavior, the technology is vulnerable to unpredictable exploitation methods (Shayegan et al, 2022;Xu, 2016). This prompted the development of specific techniques of anomaly detection.…”
Section: Aml/cft and Blockchain Forensicsmentioning
confidence: 99%
“…The goal is to single out rare or suspicious events/items-i.e., those significantly different from the dataset (Kamišalić et al, 2021). While collective anomaly detection methods target groups of data points that differ from most of the data, point anomaly detection also considers single data points (Li et al, 2022;Shayegan et al, 2022). AML/CFT-regulated entities, especially in the financial industry, deploy RegTech solutions to screen their operations and detect anomalous activities in an automated way.…”
Section: Anomaly Detection Approachesmentioning
confidence: 99%